SpTIA-1 suppresses WSSV infection by promoting apoptosis in mud crab (Scylla paramamosain). (December 2021) - Hu, Hang; Zhao, Xinshan; Cui, Yalei; Li, Shengkang; Gong, Yi
Highlights: Sp TIA-1 is overexpressed during WSSV infection in mud crab. Sp TIA-1 suppresses WSSV infection via apoptosis promotion. Sp TIA-1 can activate caspase signaling in mud crab. Sp TIA-1 can modulate MMP (⊿ψm) by regulating ROS levels. Abstract: TIA-1 (T cell restricted intracellular antigen-1) is a kind of RNA-binding protein which serves as the downstream of CED-9 (a BCL2 homolog) and induces apoptosis under stress conditions. So far, the function of apoptosis mediated by TIA-1 has been extensively studied in higher animals, and apoptosis happens to be related to biological immune defense. However, the involvement of TIA-1 in the study of immune function during viral infection has not been clearly studied, especially in marine invertebrates. In the study, Sp TIA-1 in mud crab ( Scylla paramamosain ) was specifically identified. The Open Reading Frame (ORF) of Sp TIA-1 was consisted of 1116 nucleotide bases and encoded 372 amino acids. Besides, the results showed that the expression of Sp TIA-1 was obviously up-regulated during WSSV (White Spot Syndrome Virus) infection in hemocytes of mud crab. Furthermore, through RNAi approach, we found that Sp TIA-1 could activate Caspase-3 signaling and increase ROS levels to reduce mitochondrial membrane potential, resulting in the increase of apoptosis rate in hemocytes, which eventually suppressed WSSV multiplication in mud crab. The current study therefore improves the knowledge of antiviral immunity in mud crab and provides new insights into the innate immunity of marine crustaceans.